Integrative medicine primary care: assessing the practice model through patients' experiences - Robert L. Crocker; Amy J. Grizzle; Jason T. Hurwitz; Rick A. Rehfeld; Ivo Abraham; Randy Horwitz; Andrew Weil; Victoria Maizes (BMC, 2017)
Abstract Background The University of Arizona Integrative Health Center (UAIHC) was an innovative integrative medicine (IM) adult primary care clinic in Phoenix, Arizona. UAIHC used a hybrid payment model to deliver comprehensive healthcare that includes conventional and complementary medical treatments. Methods Fidelity measures were collected to evaluate how well the IM care delivery process matched ideals for IM. Patient experiences are presented here. Patients visiting UAIHC on 1 of 10 randomly selected days between September 2013 and February 2015 were surveyed. Patients were asked about their experience with: holistic care; promotion of health, self-care, and well-being; relationship and communication with practitioners; and overall satisfaction. Results Eighty-three patients completed surveys. Based on patient-reported experiences, UAIHC delivered IM care as defined by the practice model. Conclusions Patients received holistic care, established positive caring relationships with providers who promoted their self-care and well-being, and reported high overall satisfaction with UAIHC.